Best Practices for Obtaining Genomic Consent in Pediatric Traumatic Brain Injury Research. Issue 2 (March 2019) - Schnur, Kaylee C.; Gill, Eliana; Guerrero, Alejandro; Osier, Nicole; Reuter-Rice, Karin
Abstract : Background: Precision health relies on large sample sizes to ensure adequate power, generalizability, and replicability; however, a critical first step to any study is the successful recruitment of participants. Objectives: This study seeks to explore how the enrollment strategies used in a parent study contributed to the high consent rates, establish current best practices that can be used in future studies, and identify additional factors that contribute to consent into pediatric traumatic brain injury biobanks. Methods: Retrospective secondary analysis of data from a parent study with high consent rates was examined to explore factors affecting consent into biobanking studies. Results: Of the 76 subjects who were approached, met the eligibility criteria, and reviewed the consent form, only 16 (21.1%) declined to participate. The consented group ( n = 60) represents 64.5% of those who met the eligibility criteria upon initial screening ( n = 93) and 78.9% of those with confirmed eligibility ( n = 76). Analysis of screening data suggested there were no major barriers to consenting individuals into this pediatric traumatic brain injury biobank. Discussion: There were no demographic or research-related characteristics that significantly explained enrollment. Ethically, to obtain true informed consent, parents need to understand only their child's diagnosis, prognosis, and medical care, as well as the purpose of the proposed research and its risks and benefits. Researchers need to implement best practices, including a comprehensive review of census data to identify eligible participants to approach, a prescreening protocol, and effective consenting process to obtain informed consent so that precision care initiatives can be pursued.